An Analysis of Impoliteness Strategies in “The Devil Wears Prada” Movie - Rizqi, Nurhana Tri; Afriana, Afriana (LPPM Universitas Bumigora Mataram, 2025)
This research analyzes the impoliteness strategies used in “The Devil Wears Prada” movie, focusing on how these strategies reflect the power dynamics and emotional tensions between characters. By exploring examples of bald on-record impoliteness, positive and negative impoliteness, sarcasm or mock politeness, and withholding politeness, the study intends to reveal the implications of these strategies on the characters’ interactions, self-perception, and the overarching themes of ambition and identity in the film. This research utilized a descriptive qualitative method. Data was collected through observational and non-participatory techniques. The researcher observed the dialogue from the movie